PENGARUH SELEKSI PEGAWAI DAN PENEMPATAN PEGAWAI TERHADAP KINERJA PEGAWAI PADA PT MEGA FINANCE CABANG KABUPATEN SUKABUMI: Manajemen sumberdaya manusia - Neneng Yanti Andriani & Dede Iman Nurjaman (P3M STIE PASIM Sukabumi, 2021)
This research was conducted at PT Mega Finance Sukabumi District Branch. The research method used is a survey method. The problem that occurred at PT Mega Finance Branch of Sukabumi Regency was a decrease in employee performance due to the improper placement of employees in the appropriate positions required by the company and weak employee selection processes. The research respondents were 50employees of PT Mega Finance Branch Sukabumi asthe population, while the sampling technique used the saturated sampling method,because the sample size was quite small, so that all populations were sampled.Theinstrument was tested by using the reliability test and validity test, as well as the Classical AssumptionTest. The research data were analyzed descriptively by using the frequency and associative test with the coefficient of determination, statistical hypothesis test and multiple linear regression analysis. The results showed that: Employee Selection (X1) and Employee Placement (X2) had an influence onEmployee Performance (Y) as indicated by the determination coefficient value of 50.4%, meaning that the increase in Employee Selection and Employee Placementwhich was higher and higher would increase. effect of 50.4% on the increase in Employee Performance of PT Mega Finance Sukabumi District Branch. Theregression equation for Employee Selection and Employee Placement on Employee Performance is Y = 1.370+ (0.065) X1 + (0.632) X2, meaning that if the Constant Coefficient is 1.370, it means that if the Employee Selection (X1) and Employee Placement (X2) variables stated the value is 0, then the value ofEmployee Performance (Y) is 1.370. The coefficient b1 = 0.065, meaning that if the EmployeeSelection is increased by 1 time, the higher the Employee Performance Value will increase by 0.065. The coefficient b2 = 0.632, meaning that if the Employee Placement is increased by 1 time or increases, the Employee Performance Value will increase by 0.632